Factorial composition of the Maslach Burnout Inventory-Student Survey in Mexican university students - Blanco Ornelas, José René; Ornelas Contreras, Martha; Jurado García, Perla Jannet; Blanco Vega, Humberto; Peinado Pérez, Jesús Enrique (Acta Universitaria, 2020)
The present study aims to investigate the psychometric results proposed by Schaufeli and collaborators for the Maslach Burnout Inventory-Student Survey. The total sample comprised 1222 participants; all of them are students of a degree in Physical Education and Human Motricity offered at the Autonomous University of Chihuahua, Mexico, with a mean age of 20.67 years (SD = 1.91). The sample was randomly divided into two parts to be able to carry out parallel studies that would corroborate and verify the results obtained. The factorial structure of the questionnaire was analyzed with confirmatory factor analysis. Psychometric analysis showed that a three-factorial structure was viable and adequate. The structure of the three factors (exhaustion, cynicism and efficiency), attending to substantive and statistic criteria, showed adequate indicators of validity and reliability adjustment. In addition, the factor analysis conducted with subsamples indicated the presence of strong evidence of factor structure stability.